In-situ symbiotic nano-silicide and preparation method thereof

By performing in-situ symbiotic symbiotic with other halides in the presence of a catalyst, the preparation of high-conductivity, uniformly doped in-situ symbiotic nanosilicides is achieved, solving the problem of insufficient conductivity of nanosilicon materials and significantly improving conductivity and electrochemical properties, and reduce production costs and energy consumption.

CN115215342BActive Publication Date: 2024-12-31SICHUAN WUKE JINSI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110418324.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-19
Publication Date
2024-12-31
Estimated Expiration
2041-04-19

AI Technical Summary

Technical Problem

The existing nanosilicon materials have shortcomings in terms of electrical conductivity, especially pure nanosilicon materials have poor electrical conductivity, and the existing doping methods cannot effectively improve their internal electrical conductivity. The preparation process consumes high energy and costs high, and It is difficult to achieve nanosilicide preparation with controllable size.

Method used

By symbiotically versus silicon halide with other halides in the presence of a catalyst in situ, a high conductivity, uniform doping and uniform size in situ symbiotic nanosilicide material is prepared, using metal elements such as titanium, Zirconium, carbon, germanium, tin and silicon atomic levels are symbiotic, achieving efficient electrical conductivity improvement, and reducing production costs and energy consumption by controlling reaction conditions and post-treatment steps.

Benefits of technology

The conductivity of nano-silicon is significantly improved, reaching 106-109 times that of pure nano-silicon, achieving high purity and high yield nano-silicide preparation, and can control particle size in the range of 15-100nm, improving electrochemical performance and The feasibility of industrial production reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115215342B_ABST
    Figure CN115215342B_ABST
Patent Text Reader

Abstract

The present invention discloses an in-situ symbiotic nano-silicide and a preparation method thereof. In the method, in the presence of a catalyst, a reducing agent is used to reduce silicon halide and other halides together to achieve in-situ symbiosis at the atomic level, and an in-situ symbiotic nano-silicide with high conductivity, high yield, uniform doping, uniform size and controllable is prepared. The in-situ symbiotic nano-silicide provided by the present invention has excellent properties such as high conductivity, and the preparation method provided has low cost, low energy consumption, simple preparation process, and is easy to scale up for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of nano silicon materials, and specifically relates to a size-controllable in-situ symbiotic nano silicide material and a preparation method thereof, and especially relates to an in-situ symbiotic nano silicide material for a negative electrode of a lithium ion battery and a preparation method thereof. Background Art

[0002] In recent years, graphite has been the mainstream negative electrode material for commercial lithium-ion batteries. However, its specific capacity has reached its limit (372mAh / g), and its lithium insertion potential platform is close to the deposition potential of metallic lithium. It is easy to cause safety hazards during fast charging or low-temperature charging, which limits the application of graphite in the field of large-capacity batteries in future social development. Silicon has a theoretical specific capacity 10 times higher than graphite (4200mAh / g), a moderate lithium desorption potential (<0.5V vs Li + / Li) and abundant reserves (27.6%) have attracted close attention from researchers of lithium-ion battery anodes.

[0003] However, in the actual application process, silicon materials still have some problems: first, silicon has a significant volume effect during the charge and discharge process, which can easily lead to material pulverization and failure, resulting in a rapid decay of the cycle capacity; second, silicon materials have poor conductivity, which affects the rate performance of the battery. To address the above problems, the most effective method is to perform silicon nano-sizing, which can reduce the particle size of silicon and thus reduce the cracks caused by absolute volume expansion, effectively alleviate the collapse of the electrode structure, and thus improve the cycle stability. At the same time, silicon nano-sizing can shorten the diffusion distance of lithium ions and the conduction distance of electrons, increase the electrochemical reaction rate, and improve its rate performance.

[0004] Although silicon nanomaterials have many advantages, pure nanosilicon materials still have some shortcomings in terms of conductivity. Therefore, in order to improve the conductivity of nanosilicon, some research groups have begun to try to dope silicon nanoparticles. There are currently two main ways of doping. One is to directly coat the surface of synthesized nanosilicon, and the other is to dope nanosilicon in situ at the atomic level to improve its conductivity. The doped nanosilicon particles synthesized by the former method only improve the conductivity of the surface of the nanoparticles, and do not significantly improve the conductivity inside the particles. For example, patent CN 112110448 A provides a nitrogen-doped carbon and nano-silicon composite negative electrode material, which is a composite of nitrogen-doped carbon and existing nano-silicon particles. Patent CN 108400293 A discloses a nitrogen-doped carbon-coated silicon nanomaterial. The essence of the two patents is to composite / coat a layer of nitrogen-doped carbon material on the surface of silicon nanoparticles, but both can only improve the conductivity of the surface of nano-silicon particles, but cannot improve the conductivity inside the nano-silicon particles; in the second method, some doping elements are uneven or the preparation cost of the doping process is high, and some can only achieve surface doping of silicon nanomaterials due to the doping elements or preparation methods, and cannot achieve internal or overall uniform doping. For example, patent CN 111799460 A mixes nano-silicon with a boron source and then performs high-temperature treatment to allow boron to form substitutional doping on silicon. Boron doping can improve the intrinsic conductivity and electrochemical activity of silicon materials. However, this method cannot guarantee that boron can be uniformly doped in nano-silicon. It is still limited by the size of the nano-silicon prepared by itself, and this method requires high-temperature heat treatment, which consumes a lot of energy. The elements doped in the nano-silicon material prepared by patent CN105399099 A are four non-metallic elements: C, N, B, and P. The doping method is to introduce a gas containing non-metallic doping elements into the reaction atmosphere. The doping elements are mainly present on the surface of the nano-silicon material. This method is also unable to improve the conductivity inside the nano-silicon particles, and requires arc evaporation of silicon blocks, which is relatively dangerous and energy-intensive. Summary of the invention

[0005] In order to solve the above problems, the present invention provides an in-situ symbiotic nano-silicide material and a preparation method thereof. In the method, in the presence of a catalyst, a reducing agent is used to reduce silicon halide and other halides together to achieve in-situ symbiosis at the atomic level, and prepares in-situ symbiotic nano-silicide with high conductivity, high yield, uniform doping, uniform size and controllable. The method provided by the present invention has low cost, low energy consumption, simple preparation process, and is easy to scale up for industrial production.

[0006] In order to achieve the above object, the present invention provides an in-situ symbiotic nano-silicide, the chemical formula of which is Si a Y b, a>b>0, wherein Y is selected from at least one of titanium, zirconium, carbon, germanium and tin.

[0007] In the above technical solution provided by the present invention, the Y element and the Si element in the in-situ symbiotic nano-silicide are simultaneously reduced and symbiotic at the atomic scale, and the Y element is evenly distributed around the Si element.

[0008] In the above technical solution provided by the present invention, the in-situ symbiotic nano-silicide also contains trace impurities including metal element M, halogen X and oxygen element, wherein the total content of the impurities is not higher than 0.6%.

[0009] In the above technical solution provided by the present invention, the mass percentage of each element in the in-situ symbiotic nano-silicide is: Si≥70%, 0<Y≤30%, 0≤M≤0.1%, 0≤X≤0.2%, 0≤O≤0.3%.

[0010] Another aspect of the present invention provides a method for preparing the above-mentioned in-situ symbiotic nano-silicide material, which comprises silicon halide SiX4, other halides YX c , and the reducing agent reacts in the presence of a catalyst and is then post-treated to prepare the product.

[0011] In the technical solution provided by the present invention, the input ratio of the reactant silicon halide, other halides, reducing agent and catalyst is: the molar ratio of silicon halide and other halides is 3:1-1000:1, the molar ratio of silicon halide and reducing agent is 1:100-50:1, and the molar ratio of catalyst and reducing agent is 1:100-1000:1. In some other technical solutions provided by the present invention, the input ratio of silicon halide, reactant silicon halide, reducing agent and catalyst is preferably: the molar ratio of silicon halide and other halides is 10:1-100:1, the molar ratio of silicon halide and reducing agent is 1:4-50:1, and the molar ratio of catalyst and reducing agent is 1:20-50:1.

[0012] In some embodiments of the present invention, the molar ratio of the silicon halide and other halides is 3:1, while in other embodiments, the molar ratio of the silicon halide and other halides may be 980:1, 900:1, 300:1, 76:1, 61:1, 53:1, 40:3, 35:2, 23:1, 18:1, 8:1, 5:1, etc., that is, the molar ratio of the silicon halide and other halides may be any value in the range of 3:1-1000:1. In some embodiments of the present invention, the molar ratio of the silicon halide and the reducing agent is 1:100, while in other embodiments, the molar ratio of the silicon halide and the reducing agent may be 50:1, 40:1, 20:1, 20:3, 1:3, 1:15, 1:25, 1:40, 1:60, 1:80, 1:98, etc., that is, the molar ratio of the silicon halide and the reducing agent may be any value within the range of 1:100-50:1. In some embodiments of the present invention, the molar ratio of the catalyst and the reducing agent is 1:100, while in other embodiments, the molar ratio of the catalyst and the reducing agent may be 1000:1, 800:1, 400:1, 200:1, 200:3, 1:3, 1:15, 1:25, 1:40, 1:60, 1:80, 1:90, etc., that is, the molar ratio of the catalyst and the reducing agent may be any value in the range of 1:100-1000:1.

[0013] In the above technical solution provided by the present invention, the halogen X in the silicon halide and other halides is selected from at least one of Cl, Br, and I; wherein the silicon halide can be selected from at least one of SiCl4, SiBr4, and SiI4; other halides YX c Selected from one or more of titanium halide, zirconium halide, carbon halide, germanium halide, and tin halide, wherein the titanium halide is at least one of TiCl4, TiBr4, and TiI4, the zirconium halide is at least one of ZrCl4, ZrBr4, and ZrI4; the carbon halide is at least one of CCl4, CBr4, and CI4, the germanium halide is at least one of GeCl4, GeBr4, and GeI4, and the tin halide is at least one of SnCl4, SnBr4, and SnI4.

[0014] In the technical solution provided by the present invention, the reducing agent is a metal reducing agent M, which is selected from at least one or more of Li, Na, K, Mg, Ca, Al, Rb, Cs, Sr, and Ba, where "multiple" can be a simple physical mixture of multiple metals or an alloy formed by multiple metals.

[0015] In the technical solution provided by the present invention, the catalyst is a liquid catalyst selected from one or more of ethers, esters, nitriles, sulfones, and ionic liquids. It can be a combination of substances in different categories, a combination of multiple substances in the same category, or a single compound. For example, in some embodiments of the present invention, the liquid catalyst is selected from ethers and esters, in other embodiments, the liquid catalyst is selected from ethers and sulfones, and in other embodiments, the liquid catalyst is a mixture of two ether compounds or a certain ether compound.

[0016] In the technical solution provided by the present invention, the ether liquid catalyst referred to in the present invention includes CH3O(CH2CH2O) n CH3 (n is a positive integer), ethyl ether, propyl ether, methyl ethyl ether, ethylene glycol diethyl ether, ethylene glycol di-n-butyl ether, diethylene glycol dibutyl ether, anisole, p-xylyl ether, cyclic ether, dibutyl ether, methyl tert-butyl ether, tributyl methyl ether, n-hexyl ether, isopropyl ether; ester catalysts include ethyl formate, ethyl acetate, methyl formate, methyl acetate, isobutyl acetate, butyl acetate; nitrile catalysts include acetonitrile, propionitrile, butyronitrile, succinonitrile, trimethoxypropionitrile; sulfone catalysts include DMSO, cyclopentane sulfone; the ionic liquid includes 1-alkyl-3-methylimidazole halogenide, 1-alkyl-3-methylimidazole tetrafluoroborate, 1-alkyl-3-methylimidazole hexafluoroborate, 1-alkyl-3-methylimidazole bis(trifluoromethyl)imide.

[0017] In the technical solution provided by the present invention, the reactants silicon halide, other halides, reducing agent and catalyst are reacted at a temperature of -30°C to 130°C, while the water content and oxygen content in the reaction gas atmosphere are controlled to be <200ppm and <200ppm, and the reaction is carried out while being dispersed according to a certain feeding method, and the reaction time is 1h-100h.

[0018] The method of adding the reactants silicide, other halides, reducing agent and catalyst in the present invention includes but is not limited to adding the four at the same time according to a proportion, or adding the reducing agent first according to a proportion and then slowly adding the silicide and the catalyst separately or after mixing them evenly. The slow adding method includes but is not limited to spraying addition and titration addition.

[0019] In the present invention, the dispersion methods of the reactants silicon halide, other halides, reducing agent and catalyst include, but are not limited to, one or more of stirring dispersion, mechanical crushing dispersion or ultrasonic dispersion. In some embodiments of the present invention, silicon halide, other halides, reducing agents and catalysts react at a temperature of -30°C. In other embodiments, silicide, other halides, reducing agents and catalysts may react at -25°C, -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 50°C, 55°C, 60°C, 70°C, 75°C, 80°C, 90°C, 95°C, 100°C, 110°C, 115°C, 120°C, 125°C, 130°C, etc., i.e., at any temperature between -30°C and 130°C. However, the control of the reaction temperature generally depends on the melting point or boiling point of the silicide and catalyst during the reaction. The reaction temperatures may be slightly different if different silicides and catalysts are selected.

[0020] In some embodiments of the present invention, the water content in the reaction gas atmosphere is 180ppm. In other embodiments, the water content in the reaction gas atmosphere may be 180ppm, 190ppm, 195ppm, 198ppm, 186ppm, 188ppm, 182ppm, 170ppm, 172ppm, 174ppm, 178ppm, 160ppm, 165ppm, 150ppm, 155ppm, 140ppm, 145ppm, 130ppm, 120ppm, 110ppm, 100ppm, 90ppm, 80ppm, 70ppm, 50ppm, 40ppm, 30ppm, 20ppm, etc., that is, the water content in the reaction gas atmosphere is any value between 0ppm and 200ppm.

[0021] In some embodiments of the present invention, the oxygen content in the reaction gas atmosphere is 180ppm, and in other embodiments, the oxygen content in the reaction gas atmosphere is 180ppm, 190ppm, 195ppm, 198ppm, 186ppm, 188ppm, 182ppm, 170ppm, 172ppm, 174ppm, 178ppm, 160ppm, 165ppm, 150ppm, 155ppm, 140ppm, 145ppm, 130ppm, 120ppm, 110ppm, 100ppm, 90ppm, 80ppm, 70ppm, 50ppm, 40ppm, 30ppm, 20ppm, etc., that is, the oxygen content in the reaction gas atmosphere is any value between 0ppm and 200ppm.

[0022] The present invention controls the oxygen and water content in the gas atmosphere during the reaction process, thereby effectively preventing the synthesized in-situ symbiotic silicide material from forming an oxide layer and the silicide and water from reacting to generate impurities, while also avoiding subsequent complex post-processing, reducing the entire synthesis process, and reducing production costs. The synthesized in-situ symbiotic silicide that is essentially free of an oxide layer has greatly improved performance in battery applications, especially in lithium batteries.

[0023] In some embodiments of the present invention, the reaction time of the reactants silicon halide, other halides, reducing agent and catalyst is 1 hour, while in other embodiments, the reaction time of silicide, other halides, reducing agent and catalyst can be 2 hours, 5 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 50 hours, 55 hours, 60 hours, 65 hours, 70 hours, 75 hours, 80 hours, 85 hours, 90 hours, 95 hours, 100 hours, etc., that is, the reaction time can take any value between 1 hour and 100 hours.

[0024] In the technical solution provided by the present invention, after the reactants silicon halide, other halides, reducing agent and catalyst are added in a certain proportion and react under certain conditions, certain post-treatment is required, wherein the post-treatment steps include:

[0025] (1) Separating the mixture obtained after the reaction, removing part or all of the reactants and catalysts that have not reacted fully, and obtaining the in-situ symbiotic nano-silicide Si a Y b A solid mixture;

[0026] (2) The obtained in-situ symbiotic nano-silicide Si a Y b The solid mixture is separated and dried by utilizing the difference in physical and / or chemical properties of each component to obtain the finished product in-situ symbiotic nano-silicide Si a Y b .

[0027] In the post-processing scheme provided by the present invention, the separation method in step 1) includes one or more of drying after suction filtration, drying after pressure filtration, distillation, drying after pressing, spray drying, and drying after centrifugation; the separation by utilizing the difference in physical and / or chemical properties of the components in the post-processing step 2) is to utilize the difference in physical and / or chemical properties of the components in the solid mixture to treat them in a specific solvent before separation, wherein the specific solvent is selected from one or more of methanol, ethanol, propanol, anhydrous hydrochloric acid, anhydrous hydrobromic acid, anhydrous hydroiodic acid, anhydrous nitric acid, anhydrous pyridine phosphate, acetone, ether, benzene, dichloromethane, chloroform, carbon tetrachloride, ethylene glycol, isopropanol, and isopentanol; the separation method includes dissolving and suction filtration, dissolving and pressing filtration, dissolving and centrifuging, and dissolving and pressing; and the drying is drying in an inert gas or vacuum atmosphere at 50° C.-200° C. for 10 min-300 min.

[0028] It should be noted that in the above-mentioned post-treatment method, both step 1) and step 2) are not limited to one step in the above-mentioned technical solution of the present invention, and can be performed in multiple steps. For example, in step 1), "separating the mixture obtained after the reaction to remove part or all of the reactants and catalysts that have not reacted sufficiently", in some embodiments, one separation method can be directly used to perform one or more operations to remove the reactants and catalysts that have not reacted sufficiently, leaving a mixture of "solid in-situ symbiotic nano-silicide products and halide salts" or "solid in-situ symbiotic nano-silicide products, halide salts and reactants such as reduced metals that have not reacted sufficiently"; in other embodiments, multiple separation methods (such as first using a large-pore filter membrane to filter to remove the reduced metal, and then distilling to remove the liquid reactants and catalysts) can be used to perform one or more operations to remove the reactants such as the liquid reactants that have not reacted sufficiently, the catalyst, and the reduced metal, respectively, so as to finally achieve the purpose of obtaining a mixture of solid in-situ symbiotic nano-silicide products and halide salts. The "separation by utilizing the differences in the physical and / or chemical properties of the components therein" mentioned in step 2) means utilizing the differences in the physical and / or chemical properties of the components in the solid mixture to treat them in a specific solvent before separation. The separation in this step is not limited to one step, but can be carried out in multiple steps, and each step can be repeated one or more times until a high-purity in-situ symbiotic nano-silicide product is obtained.For example, in some embodiments of the present invention, if solid reactants such as reducing metals are retained / remaining in the reaction, in some embodiments of this step, the solid reactants can be first reacted in one or more mixed solvents of methanol, ethanol, propanol, anhydrous hydrochloric acid, anhydrous hydrobromic acid, anhydrous hydroiodic acid, anhydrous nitric acid, and anhydrous phosphoric acid to remove them, and then the in-situ symbiotic nano-silicide and halide salts can be used in "pyridine, acetone, ether, benzene, dichloromethane, chloroform, carbon tetrachloride, methanol, ethanol, propanol, ethylene glycol, isopropanol, The solid mixture treated in step 1) can be separated by the difference in physical solubility in one or more mixed solvents of "isoamyl alcohol, glycerol", so as to obtain high-purity in-situ symbiotic nano-silicide, and the above two steps can be repeated once or multiple times until a high-purity in-situ symbiotic nano-silicide product is obtained; in other embodiments, if the retained / remaining solid reactant particles are large, the difference in physical properties can be directly used to dissolve the solid mixture treated in step 1) in "pyridine, acetone, ether, benzene, dichloromethane, chloroform, carbon tetrachloride, methanol, etc." In one or more mixed solvents selected from the group consisting of alcohol, ethanol, propanol, ethylene glycol, isopropanol, isopentanol, and glycerol, large particles of reducing metal are first filtered out using a sieve with a larger pore size, and then filtered using a filter membrane with a smaller pore size so that the halide salt remains in the filtrate and the in-situ symbiotic nano-silicide particles remain on the filter membrane, thereby achieving the purpose of separation and purification, and the above two steps can be repeated once or multiple times until a high-purity in-situ symbiotic nano-silicide product is obtained; in some other embodiments of the present invention, if no solid reactants such as reducing metals are left For the residue / residue, the solid mixture treated in step 1) can be directly dissolved in one or more mixed solvents of "pyridine, acetone, ether, benzene, dichloromethane, chloroform, carbon tetrachloride, methanol, ethanol, propanol, ethylene glycol, isopropanol, isopentanol, and glycerol", and filtered through a filter membrane with a smaller pore size so that the halide salt is retained in the filtrate and the in-situ symbiotic nano-silicide particles are retained on the filter membrane, thereby achieving the purpose of separation and purification, and the above steps can be performed once or repeatedly multiple times until a high-purity in-situ symbiotic nano-silicide product is obtained. The specific solvent is one or more of methanol, ethanol, propanol, anhydrous hydrochloric acid, anhydrous hydrobromic acid, anhydrous hydroiodic acid, anhydrous nitric acid, anhydrous phosphoric acid, pyridine, acetone, ether, benzene, dichloromethane, chloroform, carbon tetrachloride, ethylene glycol, isopropanol, isopentanol, and glycerol; the separation method is one or more of suction filtration, filter pressure, centrifugation, and pressing; and drying refers to drying in an inert gas or vacuum atmosphere at 50°C-200°C for 10min-300min.

[0029] The "drying" treatment mentioned in the post-treatment step 2) of the present invention includes, but is not limited to, one or more of static drying, spray drying, rotary evaporation drying, and stirring drying.

[0030] In the technical solution provided by the present invention, after the reactants silicon halide, other halides, reducing agent and catalyst are added in a certain proportion and react under certain conditions, what is obtained is an in-situ symbiotic nano-silicide cluster. The cluster is particles of in-situ symbiotic nano-silicide that are agglomerated together due to intermolecular forces. The size of the cluster particles is in the range of 0.1-20um, and the particle size of the in-situ symbiotic nano-silicide in the cluster is 15nm~100nm.

[0031] In the above technical solution of the present invention, the preparation of in-situ symbiotic nano-silicide may further include a further heat treatment after the post-treatment step 1) or step 2), wherein the heat treatment is carried out in an inert gas or vacuum atmosphere at 260°C-1300°C for 0.1h-25h. In some embodiments of the present invention, the in-situ symbiotic nano-silicide obtained after the post-treatment step 1) may be directly treated. a Y b The solid mixture is further treated, and then the post-treatment step 2) is followed to prepare the final product, the in-situ symbiotic nano-silicide, and the treatment method includes heat treatment, wherein the heat treatment is carried out in an inert gas or vacuum atmosphere at 260°C-1300°C for 0.1h-25h; in other embodiments of the present invention, the finished in-situ symbiotic nano-silicide obtained after the post-treatment step 2) is further treated to obtain the final product, the in-situ symbiotic nano-silicide, and the treatment method includes heat treatment, wherein the heat treatment is carried out in an inert gas or vacuum atmosphere at 260°C-1300°C for 0.1h-25h; in some other embodiments, the in-situ symbiotic nano-silicide treated according to the post-treatment step is directly used as the final product without further heat treatment.

[0032] In some embodiments provided by the present invention, the heat treatment temperature is 280°C, and in other embodiments, the heat treatment temperature is 300°C, 310°C, 320°C, 380°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1180°C, 1190°C, 1250°C, 1300°C, etc., that is, the heat treatment temperature is any value in the range of 260°C-1300°C; in a technical solution provided by the present invention, the heat treatment time can also be any value in the range of 0.1h-25h. Depending on the temperature and time of the heat treatment, the crystallinity of the in-situ symbiotic nano-silicide after heat treatment will have certain differences. In the present invention, further heat treatment of the obtained in-situ symbiotic nano-silicide particles can further improve their crystallinity and reduce the dangling bonds on their surfaces, thereby improving the stability of the in-situ symbiotic nano-silicide to water and oxygen.

[0033] The in-situ symbiotic nano-silicide prepared by the present invention can be applied to batteries, especially in the preparation of negative electrode materials for lithium batteries.

[0034] The inert gas described in the present invention is selected from one or more of carbon dioxide, nitrogen, argon, helium, neon, krypton, xenon and radon.

[0035] The at least one substance mentioned in the present invention may be one of the substances mentioned above, or a mixture of two or more of the substances mentioned above.

[0036] The beneficial effects of the present invention are:

[0037] 1) The present invention provides an in-situ symbiotic nano-silicide. The material is prepared by simultaneously reducing silicon halide and other halides in the presence of a reducing agent, resulting in the symbiosis of silicon and titanium, zirconium, carbon, germanium, and tin with good conductivity, thereby increasing the conductivity of pure nano-silicon by an order of magnitude. The conductivity of the synthesized in-situ symbiotic nano-silicide can reach 10 times that of pure nano-silicon. 6 -10 9 times.

[0038] 2) The present invention provides a method for preparing in-situ symbiotic nano-silicide by low-temperature reduction. The method uses a catalyst to reduce the potential energy of the reaction, thereby reducing the temperature and pressure of the reaction, and can achieve the reduction of silicon halide and other halides under a low-temperature, non-high-pressure environment to prepare a single substance of in-situ symbiotic nano-silicide. The single substance has high conductivity, high purity (purity can reach more than 99%), high yield, and the elements inside it are uniformly doped. At the same time, during the reaction process, as the silicon halide is continuously reduced, the generated reduced metal halide can effectively block the connection of Si, so that the generated product silicon can reach the nanometer scale;

[0039] 3) Currently, there are no nano-silicides with a particle size of 15 to 100 nm on the market. In the present invention, the reaction rate is controlled by controlling the amount and proportion of the catalyst and halide substances enriched on the surface of the reducing metal, thereby effectively controlling the size of the in-situ symbiotic nano-silicide and the uniformity of the particles. The particle size of the in-situ symbiotic nano-silicide product prepared by the present invention can be controlled between 15 and 100 nm, and the particle size distribution width can be controlled between 15-40 nm. Compared with commercial nano-silicon of the same particle size, the in-situ symbiotic nano-silicide of the present invention has a higher first-week efficiency, indicating that the in-situ symbiotic elements can improve the electrochemical properties of nano-silicon.

[0040] 4) The reactants selected in the present invention are solid reducing metals and silicon halide and other halides dissolved in a liquid catalyst. In the solid-liquid mixed reaction, the silicon halide and other halides dissolved in the liquid catalyst fully wrap the solid reactants, so that the reactants can fully react, thereby greatly improving the yield;

[0041] 5) The cost of the in-situ symbiotic nano-silicide prepared by the preparation method provided by the present invention is very low. 50 The price of nano silicon products with a size of 100 nm is 500,000 yuan / ton, and the price of products with a size of 30 nm is 24 million yuan / ton. Therefore, the market price of in-situ symbiotic nano silicides with the same size and higher conductivity must be higher. The unit cost price of the in-situ symbiotic nano silicides prepared by the present invention can be controlled within the range of less than 300,000 yuan / ton. This is mainly due to the following reasons: a) The raw material silicide is a by-product of polysilicon purification, which is itself a hazardous waste and is very cheap. For example, the market price of SiCl4 is close to 3,300 yuan / ton, which is cheap. The prices of other halides are also relatively low and are used less frequently; b) The preparation conditions are simple, there is no high temperature and high pressure condition, the equipment requirements are low (domestic equipment can meet the requirements), the energy consumption is low, and the cost can be effectively reduced; c) The difference in physical properties is used to remove impurities during the post-treatment process, and the impurity removal solvent can be recycled, which can further reduce the raw material cost of the in-situ symbiotic nano-silicide; d) The in-situ symbiotic nano-silicide prepared by the present invention is basically not oxidized, and there is no need to perform subsequent operations such as removing the oxidation layer, which can further reduce its preparation cost;

[0042] 6) The process of the present invention is relatively simple, highly reproducible, and can be easily industrialized;

[0043] 7) The entire reaction process of the present invention is environmentally friendly, all solvents can be recycled, no waste liquid is generated, and no waste gas is generated during the reaction process. The only solid by-product generated is reduced metal salts, which can be recycled. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a scanning electron microscope image of the in-situ symbiotic nano-silicide obtained in Example 1;

[0045] Figure 2 These are SEM-EDS surface analysis images of the in-situ symbiotic nano-silicide obtained in Example 1, wherein (a) is a SEM image of the selected sample area, (b) is a distribution image of the silicon element in the selected sample area, and (c) is a distribution image of the tin element in the selected sample area, wherein the black color is the background plate. DETAILED DESCRIPTION

[0046] The following are preferred embodiments of the present invention, and the protection of the present invention is not limited to the following preferred embodiments. It should be noted that for those skilled in the art, several modifications and improvements made on the basis of this invention conception all fall within the protection scope of the present invention.

[0047] The experimental methods and detection methods described in the following embodiments are all conventional methods unless otherwise specified. The reagents and materials are all commercially available unless otherwise specified, including small particles of reduced metal Li (particle size 2 mm), small particles of Na (particle size 2 mm), Mg chips (size: 10 mm*5 mm*1 mm), Mg balls (diameter 5 mm), large particles of lithium-magnesium alloy (particle size 5 mm), small particles of magnesium (particle size 2 mm), large particles of K (particle size 5 mm), small particles of Ca (particle size 2 mm), small particles of Al (particle size 2 mm), Li powder (particle size 75 μm), small particles of Rb (particle size 2 mm), small particles of Cs (particle size 2 mm), small particles of Sr (particle size 2 mm), and small particles of Ba (particle size 2 mm).

[0048] The preparation and detection method of the in-situ symbiotic nano-silicide used in the battery described in the following embodiment is:

[0049] In the application of batteries, the in-situ symbiotic nano-silicide product is directly used as the negative electrode material in lithium batteries. The slurry is prepared with the mass ratio of in-situ symbiotic nano-silicide: SP: polyvinylidene fluoride (PVDF) = 6:2:2, coated on 8μm copper foil, dried in a blast oven at 60℃ for 2h, and then several 12mm pole pieces are cut and assembled and placed in a vacuum oven at 110℃ for 7h for drying.

[0050] After baking, quickly transfer to the glove box, use Ф14mm metal lithium sheet as the counter electrode, use single-sided ceramic diaphragm, 1 mol / L LiPF6 / (EC+DMC) (volume ratio 1:1) plus 3% VC and 3% FEC as the electrolyte, and assemble button cells in the gloves. The water and oxygen content in the glove box is controlled below 0.1ppm.

[0051] The assembled battery was subjected to charge and discharge cycle test, and the test conditions were: discharge to 5mV at 0.5C, 0.1C, and 0.05C, and charge to 1.0V at 0.1C constant current, and cycle for 2 cycles. (The material specific capacity is calculated as: charged capacity / negative electrode active material mass; the battery first week efficiency is calculated as: battery first week charge specific capacity / battery first week discharge specific capacity)

[0052] Example 1

[0053] In an environment with a water content of <100ppm, an oxygen content of <180ppm, and a temperature of 15°C, SiCl4, SnCl4, reduced metal Mg small particles, and a liquid catalyst glycol dimethyl ether are added to a reactor in a molar ratio of 15:0.75:4:14. The reduced metal Mg small particles are then evenly mixed with SiCl4, SnCl4, and the liquid catalyst glycol dimethyl ether, and then slowly titrated and added to the reactor for mechanical crushing and dispersion reaction for 86 hours. The excess liquid halide and the catalyst are separated by filter pressing and then dried, leaving the in-situ symbiotic tin-containing in-situ symbiotic nano-silicide (silicon) A mixture of tin (tin silicide) and MgCl2 is prepared, and the mixture is added to a sufficient amount of methanol (the amount of methanol is based on the molar ratio of Mg: methanol = 1:30) to dissolve the compound MgCl2 in the solvent, and separated by suction filtration. The dissolving and filtration operation is repeated three times, and the obtained in-situ symbiotic tin-containing in-situ symbiotic nano-silicide (tin silicide) is placed in a vacuum oven for evacuation, and the temperature is set to 80°C and stirred to dry for 1.5 hours, and then heat-treated at 950°C for 3 hours under a vacuum environment to obtain an in-situ symbiotic tin-containing in-situ symbiotic nano-silicide (tin silicide) with a particle size of 25-50nm. The in-situ symbiotic tin-containing in-situ symbiotic nano-silicide (tin silicide) obtained in Example 1 is characterized by ICP, SEM and EDS (energy spectrum), and the ICP characterization results are put into Table 1, and the SEM characterization results are put into Figure 1 In the EDS characterization results are placed in Figure 2 From Table 1, it can be seen that the molar percentage of silicon atoms in the product of Example 1 is 95.20%, the mass percentage is 82.61%, the molar percentage of tin atoms is 4.79%, and the mass percentage is 17.29%. The purity of the in-situ symbiotic nano-silicide containing tin is 99.90%, and the total mass percentage of impurities is only 0.10%, which is relatively high. Figure 1 The particle size of the product of Example 1 is roughly distributed between 25-50 nm. The electrochemical performance of the in-situ symbiotic tin-containing in-situ symbiotic nano-silicide (tin silicide) and pure nano-silicon in Example 1 was tested using a semiconductor characteristic analysis system with two probes. The tested conductivity was as follows: the electronic conductivity of pure nano-silicon was 1.1×10 -7 S / cm, while the electronic conductivity of the in-situ symbiotic nano-silicide (tin silicide) containing tin is 1.3S / cm, which indicates that the intrinsic conductivity of the in-situ symbiotic nano-silicide is greatly improved due to the in-situ symbiotic tin. Figure 2The SEM-EDS surface analysis characterization of the in-situ symbiotic silicon nano-sample obtained in this embodiment is performed to characterize the obtained characterization graphs, wherein (a) is a scanning electron microscope image of the selected sample area of ​​the tin-containing in-situ symbiotic nano-silicon obtained in this embodiment, (b) is a distribution diagram of the silicon element in the sample area shown in Figure (a), and (c) is a distribution diagram of the tin element in the sample area shown in Figure (a), wherein the black color is the background plate, from which it can be seen that the tin element is uniformly distributed in the silicon, indicating that the tin element is simultaneously reduced and symbiotic with the silicon at the atomic scale. In addition, it can also be seen that the amount of tin is significantly less than the amount of silicon, and therefore it is a small amount of doping, which is consistent with the test results in ICP.

[0054] Table 1 ICP characterization results of in-situ symbiotic silicide prepared in Example 1

[0055]

[0056]

[0057] The prepared in-situ symbiotic tin-containing in-situ symbiotic nano-silicide was measured according to the preparation and detection methods for application in the battery as mentioned above, and the first-week efficiency of the battery was 77.3%, and the first-week charging specific capacity was 3106 mAh / g.

[0058] Example 2

[0059] In an environment with a water content of <100ppm, an oxygen content of <160ppm, and a temperature of 25°C, SiCl4, TiCl4, small particles of reducing metal Na, and a liquid catalyst anisole are added into a reactor in a molar ratio of 2:0.02:3:75, and subjected to ultrasonic dispersion reaction for 35 hours. Excess liquid halide and catalyst are then separated directly by spray drying, leaving a mixture of in-situ symbiotic titanium-containing in-situ symbiotic nano-silicide (titanium silicide) and NaCl. The mixture is heated under an argon atmosphere. After heat treatment at 260°C for 12h, add sufficient ethylene glycol (ethylene glycol is used in a molar ratio of Na:ethylene glycol = 1:6) to dissolve the compound NaCl in the solvent, separate by suction filtration, repeat the dissolving and suction filtration operation twice, put the obtained in-situ symbiotic titanium-containing in-situ symbiotic nano-silicide into a blast oven, continuously introduce argon gas, set the temperature to 200°C, and dry for 20min, so as to obtain an in-situ symbiotic titanium-containing in-situ symbiotic nano-silicide product with a particle size of 30-65nm. The in-situ symbiotic titanium-containing in-situ symbiotic nano-silicide obtained in Example 2 is subjected to ICP characterization, and the ICP characterization results are put into Table 2. It can be seen from Table 2 that the molar percentage of silicon atoms in the product of Example 2 is 99.00%, the mass percentage is 98.38%, and the molar percentage of titanium atoms is 0.89%, and the mass percentage is 1.51%. The purity of the titanium-containing in-situ symbiotic nano-silicide is 99.89%, and the total mass percentage of impurities is only 0.11%, which is relatively high. The electrochemical performance test of the in-situ symbiotic nano-silicide (titanium silicide) containing titanium in the in-situ symbiotic state of Example 2 was carried out using a semiconductor characteristic analysis system with two probes, and its conductivity was 2.3S / cm, which indicates that the intrinsic conductivity of the in-situ symbiotic nano-silicide is greatly improved due to the in-situ symbiotic titanium of the in-situ symbiotic nano-silicide.

[0060] Table 2 ICP characterization results of in-situ symbiotic silicide prepared in Example 2

[0061] element Mole percentage of each element The mass percentage of each element Si 99.00% 98.38% Ti 0.89% 1.51% Na 0.05% 0.04% Cl 0.05% 0.06% O 0.01% 0.01%

[0062] The prepared in-situ symbiotic titanium-containing in-situ symbiotic nano-silicide product was measured according to the preparation and detection method for application in the battery as mentioned above, and the first-week efficiency of the battery was 78.1%, and the first-week charging specific capacity was 3196 mAh / g.

[0063] Example 3

[0064] In an environment with a water content of <100ppm, an oxygen content of <100ppm, and a temperature of -3°C, silicon compounds SiCl4, CI4, reduced metal Li small particles, and liquid catalyst ethylene glycol dibutyl ether are added to a reactor in a molar ratio of 1:0.02:3:60, and then SiCl4, CI4, and liquid catalyst ethylene glycol dibutyl ether are evenly mixed and slowly sprayed and added to the stirred and dispersed reaction for 48 hours, and then excess liquid halide and catalyst are separated and dried by distillation to leave a mixture of in-situ symbiotic carbon-containing in-situ symbiotic nano-silicide and trace amounts of inadequately reacted CI4 compounds LiCl and LiI, and the mixture is added to sufficient methanol to remove trace amounts of inadequately reacted The reacted CI4 is then filtered to obtain a mixture of in-situ symbiotic carbon-containing in-situ symbiotic nano-silicide, compounds LiCl and LiI, the mixture is added to a sufficient amount of pyridine, the compounds LiCl and LiI are dissolved in ethanol (the amount of ethanol is based on the molar ratio of Li:ethanol = 1:20), and separated by centrifugation, and the dissolution and centrifugation operation is repeated four times, the obtained in-situ symbiotic carbon-containing in-situ symbiotic nano-silicide is placed in a vacuum oven and evacuated, the temperature is set to 60°C and allowed to stand and dry for 4 hours, and then the dried in-situ symbiotic carbon-containing in-situ symbiotic nano-silicide is subjected to a heat treatment at 700°C for 2 hours in a vacuum environment to obtain an in-situ symbiotic carbon-containing in-situ symbiotic nano-silicide product with a particle size range of 30-65nm. The in-situ symbiotic carbon-containing in-situ symbiotic nano-silicide (silicified carbon) obtained in Example 3 was subjected to ICP characterization, and the ICP characterization results were put into Table 3. It can be seen from Table 3 that the molar percentage of silicon atoms in the product of Example 3 is 98.50%, the mass percentage is 99.30%, the molar percentage of carbon atoms is 1.3%, and the mass percentage is 0.56%; the purity of the in-situ symbiotic nano-silicide containing carbon is 99.86%, and the total mass percentage of impurities is only 0.14%, which is relatively high in purity. The electrochemical performance test of the in-situ symbiotic carbon-containing in-situ symbiotic nano-silicide (silicified carbon) and pure in-situ symbiotic nano-silicide in Example 3 was carried out using a semiconductor characteristic analysis system using two probes, and the conductivity was 5.2×10S / cm, which shows that the in-situ symbiotic nano-silicide has greatly improved the intrinsic conductivity of the in-situ symbiotic nano-silicide due to the in-situ symbiotic carbon.

[0065] Table 3 ICP characterization results of in-situ symbiotic silicide prepared in Example 3

[0066] element Mole percentage of each element The mass percentage of each element Si 98.50% 99.30% C 1.30% 0.56% Li 0.05% 0.01% Cl 0.05% 0.07% O 0.10% 0.06%

[0067] The prepared in-situ symbiotic tin-containing in-situ symbiotic nano-silicide product was measured according to the preparation and detection method for application in the battery as mentioned above, and the first-week efficiency of the battery was 77.5%, and the first-week charging specific capacity was 3142 mAh / g.

[0068] Example 4

[0069] In an environment with a water content of <120ppm, an oxygen content of <150ppm, and a temperature of -5°C, silicon compounds SiCl4, ZrCl4, reduced metal Mg particles, and a liquid catalyst (50% ethylene glycol dimethyl ether, 50% dimethyl sulfoxide (DMSO) in a molar ratio of 3:0.09:3:85) were added to a reactor and stirred and ultrasonically dispersed for 20 hours. The excess liquid halide and catalyst were separated by suction filtration and then dried, leaving a trace amount of ZrCl4 that was not fully reacted, and the in-situ symbiotic content A mixture of an in-situ symbiotic nano-silicide of zirconium and a compound MgCl2 is added to a sufficient amount of methanol (the amount of methanol is based on a molar ratio of Mg:methanol = 1:25) to dissolve the compound MgCl2 in the solvent, and a trace amount of ZrCl4 that has not fully reacted reacts with methanol and then dissolves in the solvent, and is separated by a filter press method, and the dissolution and filter press operation is repeated four times, and the obtained in-situ symbiotic nano-silicide containing zirconium is placed in a vacuum oven and evacuated, and the temperature is set to 70°C and left to dry for 3 hours, and then the dried The good in-situ symbiotic zirconium-containing in-situ symbiotic nano-silicide was subjected to a heat treatment at 1100°C for 3 hours in a vacuum environment to obtain an in-situ symbiotic zirconium in-situ symbiotic nano-silicide product with a particle size of 30-60nm. The in-situ symbiotic zirconium-containing in-situ symbiotic nano-silicide (zirconium silicide) obtained in Example 4 was subjected to ICP characterization, and the ICP characterization results were put into Table 4. It can be seen from Table 4 that the molar percentage of silicon atoms in the product of Example 4 is 97.20%, the mass percentage is 92.12%, and the molar percentage of zirconium atoms is 2 .50%, and the mass percentage is 7.70%. The purity of the zirconium-containing in-situ symbiotic nano-silicide is 99.82%, and the total mass percentage of impurities is only 0.18%, which is relatively high in purity. The electrochemical performance test of the in-situ symbiotic zirconium-containing in-situ symbiotic nano-silicide (zirconium silicide) in Example 4 was carried out using a semiconductor characteristic analysis system with two probes. Its conductivity is 1.4×10S / cm, which shows that the in-situ symbiotic nano-silicide has a greatly improved intrinsic conductivity due to the in-situ symbiotic zirconium.

[0070] Table 4 ICP characterization results of in-situ symbiotic silicide prepared in Example 4

[0071] element Mole percentage of each element The mass percentage of each element Si 97.20% 92.12% Zr 2.50% 7.70% Li 0.05% 0.01% Cl 0.05% 0.06% O 0.20% 0.11%

[0072] The prepared in-situ symbiotic zirconium-containing in-situ symbiotic nano-silicide product was measured according to the preparation and detection method for application in the battery as mentioned above, and the first-week efficiency of the battery was 77.6%, and the first-week charging specific capacity was 3173 mAh / g.

[0073] Example 5

[0074] In an environment with a water content of <100ppm, an oxygen content of <160ppm, and a temperature of 15°C, silicon compounds SiCl4, GeCl4, large particles of reducing metal K, and a liquid catalyst (50% ethylene glycol dimethyl ether, 50% ethylene glycol diethyl ether) are added to a reactor in a molar ratio of 100:0.1:1:1000, and stirred and dispersed for 60 hours. Excess liquid halide and catalyst are separated and dried by filter pressing, leaving a mixture of in-situ symbiotic nanosilicide of in-situ symbiotic germanium and compound KCl, and the mixture is added to The in-situ symbiotic nano-silicide containing germanium is placed in a vacuum oven and evacuated, and the temperature is set to 80°C and allowed to stand for drying for 4 hours. The dried in-situ symbiotic nano-silicide containing germanium is then subjected to a heat treatment of 1000°C for 3 hours under a vacuum environment to obtain an in-situ symbiotic nano-silicide product containing germanium with a particle size of 35-70 nm. The in-situ symbiotic nano-silicide containing germanium (germanium silicide) obtained in Example 5 is subjected to ICP characterization, and the ICP characterization results are shown in Table 5. As shown in Table 5, the molar percentage of silicon atoms in the product of Example 5 is 99.70%, the mass percentage is 99.67%, and the molar percentage of germanium atoms is 0.10%, the mass percentage is 0.27%. The purity of the in-situ symbiotic nano-silicide containing germanium is 99.94%, and the total mass percentage of impurities is only 0.04%, which is relatively high. The electrochemical performance test of the in-situ symbiotic nano-silicide (germanium silicide) containing germanium in the in-situ symbiotic manner of Example 5 was carried out using a semiconductor characteristic analysis system with two probes, and its conductivity was 0.41S / cm, which shows that the intrinsic conductivity of the in-situ symbiotic nano-silicide is greatly improved due to the in-situ symbiotic germanium of the in-situ symbiotic nano-silicide.

[0075] Table 5 ICP characterization results of in-situ symbiotic silicide prepared in Example 5

[0076] element Mole percentage of each element The mass percentage of each element Si 99.8% 99.67% Ge 0.1% 0.27% K 0.01% 0.01% Cl 0.01% 0.01% O 0.08% 0.04%

[0077] The prepared in-situ symbiotic zirconium-containing in-situ symbiotic nano-silicide product was measured according to the preparation and detection method for application in the battery as mentioned above, and the first-week efficiency of the battery was 77.7%, and the first-week charging specific capacity was 3189 mAh / g.

[0078] Comparative Example

[0079] In an environment with a water content of <100ppm, an oxygen content of <180ppm, and a temperature of 15°C, SiCl4, small particles of reduced metal Mg, and a liquid catalyst glycol dimethyl ether are added to a reactor in a molar ratio of 15:4:14. The small particles of reduced metal Mg are then evenly mixed with the SiCl4 and the liquid catalyst glycol dimethyl ether and then slowly titrated and mechanically crushed and dispersed for 86 hours. The excess liquid halide and the catalyst are separated and dried by filter pressing, leaving a mixture of nano-silicon and MgCl2. The mixture is added to a sufficient amount of methanol (the amount of methanol is based on a molar ratio of Mg:methanol = 1:30), the compound MgCl2 is dissolved in the solvent, and the mixture is separated by suction filtration. The dissolution and suction filtration operation is repeated three times, and the obtained nano-silicon is placed in a vacuum oven for evacuation, the temperature is set to 80°C, and the mixture is stirred and dried for 1.5 hours. The nano-silicon is then heat-treated at 950°C for 3 hours under vacuum to obtain a particle size of 25-50nm.

[0080] The electrochemical performance of pure nano-silicon prepared in comparison was tested using a semiconductor characteristic analysis system with two probes. The conductivity tested was: the electronic conductivity of pure nano-silicon was 1.1×10 -7 The nano silicon product obtained in the comparative example was applied to the battery according to the above preparation and detection method to obtain a battery with a first-week efficiency of 74.6% and a first-week charging capacity of 3243 mAh / g.

[0081] Table 6 Important parameters such as raw materials, ratios, reaction conditions, etc. in Examples 1-5 and Comparative Examples are shown below.

[0082]

[0083] Table 7 Performance test parameters of the in-situ symbiotic nano-silicides synthesized in Examples 1-5 and the nano-silicon synthesized in the comparative example

[0084]

[0085] It can be seen from the above table that the doped titanium, germanium, carbon, tin, zirconium and other elements have different degrees of lower conductivity and first-cycle charge capacity than silicon. However, after doping the above elements into silicon nanoparticles by in-situ symbiosis, not only did the first-cycle charge capacity of nano-silicon not be reduced, but due to the incorporation of the above elements, the conductivity of the finally prepared in-situ symbiotic nano-silicide was improved, thereby reducing the internal resistance of the battery electrode and improving the first-cycle efficiency of the battery.

[0086] In the description of this specification, the description with reference to the terms "some embodiments", "other embodiments", "embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0087] Although the embodiments and examples of the present invention have been shown and described above, it can be understood that the above embodiments and examples are exemplary and cannot be construed as limitations on the present invention. A person skilled in the art can change, modify, replace and modify the above embodiments and examples within the scope of the present invention.

Claims

1. A method for preparing in-situ symbiotic nano-silicide, characterized in that: The in-situ symbiotic nano-silicide is composed of halogenated silicon SiX4, other halides YX c , a reducing agent is reacted in the presence of a catalyst and then post-treated to prepare the product; The post-processing comprises the following steps: (1) Separating the mixture obtained after the reaction, removing part or all of the reactants and catalysts that have not reacted fully, and obtaining the in-situ symbiotic nano-silicide Si a Y b A solid mixture; (2) The obtained in-situ symbiotic nano-silicide Si a Y b The solid mixture is separated and dried by utilizing the difference in physical and / or chemical properties of each component to obtain the finished product in-situ symbiotic nano-silicide Si a Y b ; The preparation of the finished in-situ symbiotic nano-silicide further comprises a further heat treatment after step (1) or step (2), wherein the heat treatment is carried out in an inert gas or vacuum atmosphere at 260° C. to 1300° C. for 0.1 h to 25 h; The chemical formula of the in-situ intergrowth nano-silicide is Si a Y b , a>b>0, wherein Y is selected from at least one of titanium, zirconium, carbon, germanium and tin; the mass percentages of Si and Y elements in the in-situ symbiotic nano-silicide are respectively: 99.67%≥Si≥70%, 0.27≤Y≤30%; In the in-situ symbiotic nano-silicide, the Y element and the Si element are simultaneously reduced and symbiotic at the atomic scale, and the Y element is evenly distributed around the Si element; the in-situ symbiotic nano-silicide also contains trace impurities including metal element M, halogen X and element O, wherein the total content of the impurities is not higher than 0.6%; The halogen X in the silicon halide and other halides is selected from at least one of Cl, Br and I; The other halide YXc is one or more of titanium halide, zirconium halide, carbon halide, germanium halide, and tin halide; The reducing agent is a metal reducing agent M; the catalyst is a liquid catalyst; The molar ratio of each component in the reaction system is: silicon halide: reducing agent is 1:100-50:1, silicon halide: other halides is 3:1-1000:1, catalyst: reducing agent is 1:100-1000:1; The catalytic reaction is dispersed and reacted for 1h-100h in a gas atmosphere with a temperature of -30°C to 120°C, a water content of <200ppm, and an oxygen content of <200ppm; The metal reducing agent M is at least one of Li, Na, K, Mg, Ca, Al, Rb, Cs, Sr, and Ba; The liquid catalyst is selected from one or more of ethers and sulfones.

2. The method for preparing in-situ symbiotic nano-silicide according to claim 1, wherein the ether liquid catalyst comprises CH3O (CH2CH2O) n CH3, ethyl ether, ethylene glycol diethyl ether, ethylene glycol di-n-butyl ether, diethylene glycol dibutyl ether, anisole, p-xylyl ether, cyclic ether, dibutyl ether, methyl tert-butyl ether, n-hexyl ether, isopropyl ether, wherein n is a positive integer; sulfone catalysts include DMSO and cyclopentane sulfone.

3. The method for preparing in-situ symbiotic nano-silicide according to claim 1, characterized in that: The separation methods described in step (1) include drying after suction filtration, drying after filter pressing, distillation, spray drying, and drying after centrifugation; the separation described in step (2) utilizing the difference in physical and / or chemical properties of the components therein is to utilize the difference in physical and / or chemical properties of the components in the mixture to treat them in a specific solvent before separation, and the specific solvent is selected from one or more of methanol, ethanol, propanol, acetone, ether, benzene, dichloromethane, chloroform, carbon tetrachloride, ethylene glycol, isopropanol, and isopentanol; the separation methods described in step (2) include dissolving and suction filtration, dissolving and filter pressing, and dissolving and centrifuging, and the drying is drying in an inert gas or vacuum atmosphere at 50°C-200°C for 10min-300min.

4. An in-situ symbiotic nano-silicide, characterized in that: The in-situ symbiotic nano-silicide is prepared by the preparation method according to any one of claims 1 to 3.

5. The in-situ symbiotic nano-silicide according to claim 4, characterized in that: The mass percentage of trace impurities in the in-situ symbiotic nano-silicide is: 0≤M≤0.1%, 0≤X≤0.2%, 0≤O≤0.3%.